Bio‐inspired Nonheme Iron Oxidation Catalysis: Involvement of Oxoiron(V) Oxidants in Cleaving Strong C−H Bonds. Issue 19 (2nd March 2020) - Kal, Subhasree; Xu, Shuangning; Que, Lawrence
Abstract: Nonheme iron enzymes generate powerful and versatile oxidants that perform a wide range of oxidation reactions, including the functionalization of inert C−H bonds, which is a major challenge for chemists. The oxidative abilities of these enzymes have inspired bioinorganic chemists to design synthetic models to mimic their ability to perform some of the most difficult oxidation reactions and study the mechanisms of such transformations. Iron‐oxygen intermediates like iron(III)‐hydroperoxo and high‐valent iron‐oxo species have been trapped and identified in investigations of these bio‐inspired catalytic systems, with the latter proposed to be the active oxidant for most of these systems. In this Review, we highlight the recent spectroscopic and mechanistic advances that have shed light on the various pathways that can be accessed by bio‐inspired nonheme iron systems to form the high‐valent iron‐oxo intermediates. Abstract : Iron‐oxygen intermediates like iron(III)‐hydroperoxo and high‐valent iron‐oxo species have been trapped and identified in investigations of bio‐inspired catalytic nonheme iron systems, with the latter proposed to be the active oxidant for most of these systems. This Review highlights recent spectroscopic and mechanistic advances that have shed light on the pathways that can be accessed by these systems to form high‐valent iron‐oxo intermediates.